Using lean principles to introduce intraoperative navigation for scoliosis surgery. (January 2020) - Cawley, Derek T.; Rajamani, Vijay; Cawley, Michael; Selvadurai, Susanne; Gibson, Alexander; Molloy, Sean
Abstract : Aims: Intraoperative 3D navigation (ION) allows high accuracy to be achieved in spinal surgery, but poor workflow has prevented its widespread uptake. The technical demands on ION when used in patients with adolescent idiopathic scoliosis (AIS) are higher than for other more established indications. Lean principles have been applied to industry and to health care with good effects. While ensuring optimal accuracy of instrumentation and safety, the implementation of ION and its associated productivity was evaluated in this study for AIS surgery in order to enhance the workflow of this technique. The aim was to optimize the use of ION by the application of lean principles in AIS surgery. Methods: A total of 20 consecutive patients with AIS were treated with ION corrective spinal surgery. Both qualitative and quantitative analysis was performed with real-time modifications. Operating time, scan time, dose length product (measure of CT radiation exposure), use of fluoroscopy, the influence of the reference frame, blood loss, and neuromonitoring were assessed. Results: The greatest gains in productivity were in avoiding repeat intraoperative scans (a mean of 248 minutes for patients who had two scans, and a mean 180 minutes for those who had a single scan). Optimizing accuracy was the biggest factor influencing this, which was reliant on incremental changes to the operating setup and technique. Conclusion: The application of lean principles to the introduction of ION for AIS surgery helps assimilate this method into the environment of the operating theatre. Data and stakeholder analysis identified a reproducible technique for using ION for AIS surgery, reducing operating time, and radiation exposure. Cite this article: Bone Joint J. 2020;102-B(1):5–10